2019
DOI: 10.1021/acs.jafc.9b03316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking and Barbecuing on the Contents of Anthraquinone (ATQ) and Polycyclic Aromatic Hydrocarbons (PAHs) in Frankfurter-Type Sausages

Abstract: The contents of anthraquinone (ATQ) and polycyclic aromatic hydrocarbons (anthracene (ANT) and PAH4) in smoked Frankfurter-style sausages were investigated depending on various smoking conditions. During smoking, the smoke generator, the smoking duration, the type of wood, and some more plant-specific parameters were tested. The sausages were also barbecued on a charcoal grill. The lowest mean contents of all analytes were observed when friction smoke was used (ATQ < limit of quantification (LOQ); ANT < LOQ; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This evidence can be mutually supported by our previous investigation of 89 milk samples in which the parent PAHs of 9-FO and ATQ (fluorene and anthracene) were also detected in all samples. Actually, it was reported that ATQ may occur in light or thermal processes during food processing and storage. Therefore, it is reasonably assumed that these OPAHs can be produced by the oxidization of parent PAHs during thermal processing. ATQ has been classified as a 2B carcinogen by the International Agency for Research on Cancer .…”
Section: Resultsmentioning
confidence: 99%
“…This evidence can be mutually supported by our previous investigation of 89 milk samples in which the parent PAHs of 9-FO and ATQ (fluorene and anthracene) were also detected in all samples. Actually, it was reported that ATQ may occur in light or thermal processes during food processing and storage. Therefore, it is reasonably assumed that these OPAHs can be produced by the oxidization of parent PAHs during thermal processing. ATQ has been classified as a 2B carcinogen by the International Agency for Research on Cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Species of Polygonaceae, Leguminosae, Rubiaceae, and some 30 other families contain an abundance of natural antioxidants, including but are not limited to phenolic compounds. , Anthraquinones (ANQs) belong to this group but mostly have been used as colorants in food, drugs, and cosmetics. , ANQ derivatives with acidic or polar, hydrophilic substitution such as aloe-emodin, emodin, rhein, chrysophanol, and physcion were described with antiangiogenic activities. , Experimental antioxidant activity data of ANQs that were collected by the 2,2-diphenyl-1-picrylhydrazyl, total reducing power ability, oxygen radical absorbance capacity ,and low-density lipoprotein methods showed that ANQs could exhibit good antioxidant activity. , …”
Section: Introductionmentioning
confidence: 99%
“…Studies on PAH derivatives are mostly limited to atmospheric particulate matter and environmental samples [ 5 , 18 , 19 , 20 , 21 ]. However, the PAHs derivatives can, similar to PAHs, contaminate smoked products and contamination is believed to be dependent on applied smoking technology, type of wood, smoke generator and combustion temperature [ 3 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards to OPAHs, they were similarly found in beverages such as:, coffee [ 25 ], tea [ 27 ], beer [ 28 ], milk and milk powders [ 32 ]. The OPAHs were also detected in oils [ 33 , 34 , 35 , 36 , 37 ], fried products such as peanuts [ 38 ], bread [ 39 , 40 ] and barbecued or smoked foods [ 3 , 22 , 24 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation